Network structure of family function and self-management in patients with early chronic kidney disease amid the COVID-19 pandemic - Cui, Yi; Yang, Tianqi; Li, Rong; Wang, Hua; Jin, Shasha; Liu, Na; Liu, Xufeng; Liu, Hongbao; Zhang, Yinling (Frontiers in Public Health, 2023)
Background Family function plays a pivotal role in self-management among patients with early chronic kidney disease (CKD), which has been especially important during the COVID-19 pandemic. Previous studies have investigated the relationships between family function and self-management using total scores through self-report questionnaires while ignoring the different components in both family function and self-management. The specific objective of this study was to explore the network structure of family function and self-management at the component level. Methods A total of 360 patients with early CKD from three tertiary hospitals were enrolled in our cross-sectional survey from September to December 2021 in China. Components of family function were measured by the Family Adaptation Partnership Growth and Resolve Index, and components of self-management were measured by the Chronic Kidney Disease Self-management Instrument. Network analysis was used to establish the network structure. Results Edges across the community of family function and self-management were mainly positive. Edges between F3 “Growth” and M1 “Self-integration”, F2 “Partnership” and M3 “Seeking social support,” F5 “Resolve” and M3 “Seeking social support” were the strongest. F3 “Growth” had the greatest positive bridge expected influence of family function community (0.12), and M3 “Seeking social support” had the greatest positive bridge expected influence of self-management community (0.16). Conclusion We explored the potential pathways between different components of family function and self-management among patients with early CKD during the COVID-19 pandemic and found fine-grained relationships between them. The two nodes F3 “Growth” and M3 “Seeking social support” may provide a new idea from the perspective of family function for interventions to improve self-management.